Essentials in elbow surgery : a comprehensive approach to common elbow disorders - Barco, Raul; Antuna, Samuel (Springer London, 2014)
This book reflects the recent increased interest in elbow surgery as the techniques involved have allowed a greater choice of procedures for a wider variety of patients. As a result, there is a demand for a book that contains practical information about the most commonly encountered issues and how to effectively manage the surgical procedures.   Essentials is in Elbow Surgery: A Comprehensive Approach to Common Elbow Disorders provides a concise approach to common elbow practice for a general orthopaedic surgeon and a guide to learn basic elbow surgery during training. It aims to provide orthopaedic surgeons with the confidence to manage daily acute and chronic elbow problems that are routinely encountered in clinical practice. It includes contributions from some of the best elbow surgeons of the world, well known for their expertise and dedication to teaching and science. By applying this book to practice, orthopaedic surgeons will be more able to care for difficult fractures around the elbow, locate the source of the pain and plan the best treatment for their patients.